The influences of cognition of institutional logics and triple helix relations on innovation performance: An empirical study of firms in industrial park in Taiwan - YANG, Min-Lang; GONG, Rueywei; CHEN, Shih-Ying; TSAI, Fu-Sheng (Turkish Economic Review, 2017)
Abstract. The present study set out to investigate into the influences of cognition of institutional logics and triple helix relationships (i.e., the industry-university-government linkages) on firm innovation performance in the context of Taiwan industrial parks. The data from 131 organizational-level questionnaires collected from firms located in different industrial parks were analyzed. The results showed that cognition of institutional logics is positively associated with firms’ innovation performance. Furthermore, such positive relationship is strengthened by the number of triple helix relationships in the form of mediation but not moderation effect. Theoretical and practical implications were elaborated. Keywords. Cognition of institutional logics, Triple helix, Innovation performance, Industrial park. JEL. M10, M14.